The Impact of SIAkad E-Service Quality and Campus Facilities on Institutional Image Through Student Satisfaction: Case Study at STIMI-YAPMI Makassar Campus - Ibrahim Syah; Riswan Riswan; Mursalim; Endang Hermawan (PT. Maju Malaqbi Makkarana, 2026)
The digital transformation in higher education requires universities to provide not only reliable technology-based academic services but also physical facilities that support the student learning experience. This study aims to analyze the effect of the Academic Information System (SIAKAD) e-Service Quality and campus facilities on institutional image, with student satisfaction as an intervening variable. The study employed a quantitative approach with a causal associative design. Data were collected through a five-point Likert-scale questionnaire from 80 active students of STIMI-YAPMI Makassar selected using a purposive sampling technique. Data analysis was conducted using validity and reliability tests, path analysis, and the Sobel test to examine the mediating role. The results showed that e-Service Quality and physical facilities had a positive and significant effect on student satisfaction and institutional image. E-Service Quality had the most dominant influence on student satisfaction. Furthermore, student satisfaction was shown to mediate the effect of e-Service Quality on institutional image, but not the effect of physical facilities on institutional image. These results indicate that e-Service Quality shapes institutional image through student experience and satisfaction, while physical facilities act as a reputational symbol that directly influences image. This research provides theoretical contributions in the development of higher education service management models as well as practical implications for higher education managers in formulating strategies for improving service quality and strengthening the institution's image in a sustainable manner.